Strategic Analyses of the National River Linking Project (NRLP) of India Series 5. Proceedings of the Second National Workshop on Strategic Issues in Indian Irrigation, New Delhi, India, 8-9 April 2009 - International Water Management Institute (International Water Management Institute, 2009)
Research in this book is part of the project no. 48, ?Strategic Analyses of India?s National River-Linking Project (NRLP)? of the CGIAR Challenge Program on Water and Food (CPWF).